Bacterial Contamination between Computers in Computer Labs - Morooj Ali Fahad1 , Muna Hameed Ahmed2 , Shahad Nazar Mustafa1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was conducted to identify the role of computers in transmitting bacterial infections to users ofthese devices. The bacteria on the surface of computers (mouse and keyboard) were isolated to identify theirgenotypes and their effects on the health of their users. The study sample included 100 samples divided asfollows: 10 computers for each section of the Technical Institute in Baquba. Wipes grew on the followingcircles: Macconkey agar, Nutrient agar, Blood agar for its study and recognition of its shape and was dyedwith chrom. The most common species in the studied samples were Staphylococcus spp. The prevalence ofGram-positive spherical bacteria on the surface of computers (mouse and keyboard) was higher than thatof Bacillus and Gram negative bacteria. (192) isolates of computers and the percentage of contamination ofthe computer keyboard higher than the percentage of contamination of the mouse as the number of isolatesof the phenomenon of swabs taken from the keyboard (117) and the proportion of about (60.9%) while thenumber of isolates visible from swabs taken from the mouse (75%). The percentage of bacteria found onthe surface of the keyboard is more numerous than the bacteria on the mouse surface. The results of theantibiotic sensitivity test showed that all of these species were sensitive to antibiotics but to varying degrees.